A Commentary on the Parenting of Adolescents in Diverse and Multicultural Contexts. (18th August 2018) - Maholmes, Valerie
Abstract : This commentary on the Special Issue on Parenting Adolescents in Multicultural Contexts discusses key concepts addressed by the authors in this special issue. The connecting themes of parenting styles, relationships, and the need for relevant research methods and measures are discussed. The commentary concludes with reflections on these themes for the field of developmental science and important questions for developmental scientists to ponder to advance the research in this important area of inquiry.